Desenvolvimento de website educativo para conscientiza????o de crian??as sobre h??bitos saud??veis - Pereira, Raiane Maiara dos Santos (2015)
Sedentary lifestyle is increasing rapidly, affecting not only adults but children and adolescents, technological development has encouraged this lifestyle. However, this reality need tools that implementing health information, the use of educational software may promote learning and capacity to do healthy choices. Health education provides formal opportunities for students to acquire knowledge and learn essential life skills that can foster healthy behaviors, such as physical activity and healthy eating. Thus, this study aimed to develop and test an health educational website for encourages healthy choices in children. A total of thirty nine school children (twenty two girls; 18.0??3,3kg/m??; 19,2??8,9%), with ages between 8-10yr (eutrophic, level of physical activity between moderate and active, socioeconomic class "B"), students from 2nd to 5th grade of elementary school, both public (61.5%) and private schools. The website received the name TODDS Kids (Every Day Fun and Healthy). First, a pilot study was realized with 15 children. TODDS was built in HTML5 format, at the platform Wix with support of Physical Education and Nutrition professionals. Children accessed the website for one hour, when had contact with pictures, videos, stories and short texts about physical activity and healthy eating. They had opportunity to access other sites that discuss the same topic, as well as access to an educational tool to encourage healthy habits known as "Agendinha" a kind of daily colorful diary, available for download and with instructions for use. Thereafter, children answered a questionnaire to assess the perception of the site and their contents. 97.4% of children said they would like to access the site again, all of them said that could indicate the site to a friend. The colors, images and information were well evaluated (above 9.0 points). When asked about the practice of physical activity, 92.3% reported that would be more active, and 87.2% would like to eat more healthy foods. Parents were consulted, ten days after intervention, to check how the tool could have influenced the healthy behaviors, most of them related positive changes to physical activity and healthy eating of their children. Through the results, we concluded that TODDS Kids showed an efficient tool for changes in healthy lifestyles in children. However, other studies are needed with prolonged follow-up with children and their families after browsing the website.